2019
DOI: 10.1111/ijpp.12595
|View full text |Cite
|
Sign up to set email alerts
|

Competence and confidence with prescribing in pharmacy and medicine: a scoping review

Abstract: Objectives Prescribing is a growing scope of practice for pharmacists. The objective of this scoping review is to explore themes within the literature related to prescribing competence and confidence in the disciplines of pharmacy and medicine. Methods Online databases MEDLINE, EMBASE and Global Health were used to identify articles from inception to October 2018. Articles describing either the competence or confidence of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…A review of studies investigating pharmacist confidence and competency in prescribing concluded that whilst most pharmacists felt competent to prescribe, they lacked confidence. 61 Prescribing is a growing scope of practice for pharmacists, and in the UK reforms have been made to education and training so that individuals qualify as prescribers at the point of first registration as a pharmacist. 62 Interventional studies should adapt and move away from traditional physician-led prescribing models.…”
Section: Discussionmentioning
confidence: 99%
“…A review of studies investigating pharmacist confidence and competency in prescribing concluded that whilst most pharmacists felt competent to prescribe, they lacked confidence. 61 Prescribing is a growing scope of practice for pharmacists, and in the UK reforms have been made to education and training so that individuals qualify as prescribers at the point of first registration as a pharmacist. 62 Interventional studies should adapt and move away from traditional physician-led prescribing models.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of available surveys concerning pharmaceutical practices in the field of prescribing, and opinions of Polish pharmacists about the self-administration of prescriptions, a self-designed questionnaire was constructed based on articles referring to experiences with pharmaceutical prescribing in other countries [11][12][13]. The Survey questionnaire can be found at the Supplementary Materials.…”
Section: Research Toolsmentioning
confidence: 99%
“…It is also essential that Canadian undergraduate pharmacy curriculum provides opportunities for learning effective decision-making and problem-solving skills to build prescribing confidence. [27][28][29][30] What is known about educating students for contraception prescribing? Pharmacy students expressed a high level of confidence with contraceptive counselling skills but highlighted the need for more education in choosing contraception options.…”
Section: Contraception Curriculum and Training In Canadamentioning
confidence: 99%